Plasma miR-122-5p and miR-142-5p and their role in chemoresistance of patients with colon cancer - Vokacova, Klara; Landecka, Aneta; Selvi, Saba; Horak, Josef; Novosadova, Vendula; Manakova, Katerina; Levy, Miroslav; Vymetalkova, Veronika (Mutagenesis, 2025)
Chemoresistance represents a major issue affecting cancer therapy efficacy. Because microRNAs (miRNAs) regulate gene expression on multiple levels, their role in chemoresistance development is reasonably certain. In our previous study, miR-122-5p and miR-142-5p were identified as diagnostic, prognostic, and predictive biomarkers for primary and metastatic rectal cancer. The aim of the present study was to investigate whether these miRNAs can also reflect the disease course of patients with colon cancer (CC). Further, we focused on a deeper understanding of their involvement in 5-fluorouracil (5-FU) chemoresistance development.
Keywords: senioři; Prognosis; lidé; regulace genové exprese u nádorů; fluoruracil; mikro RNA; Fluorouracil; Middle Aged; mužské pohlaví; MicroRNA; chemoresistance; MicroRNAs; Biomarkers, Tumor; chemorezistence; liquid biopsy; nádory tračníku; biomarker; ženské pohlaví; nádorové biomarkery; prognóza; Humans; Gene Expression Regulation, Neoplastic; Colonic Neoplasms; lidé středního věku; Female; Aged; colon cancer; Drug Resistance, Neoplasm; Male